Accelerated brush growth on nanoparticle surfaces by reversible addition‐fragmentation chain transfer polymerization. Issue 12 (1st April 2014) - Jiao, Yang; Akcora, Pinar
ABSTRACT It is now well established that controlling the grafted chain lengths and densities on nanoparticle surfaces determines the effective interactions between particles, and their assembly. Here, we present unusual kinetic results for achieving grafted chain lengths longer than the free chains using reversible addition‐fragmentation chain transfer (RAFT) polymerization and discuss the limitations to obtaining polymer grafting density higher than ∼0.06 chains/nm2. We observe that surface initiated polymerization grows faster than the free chains in solution with high RAFT agent coverage (1.95 agents/nm2) on nanoparticles. The time‐dependence of graft density suggests that activation of the anchored chain transfer agent (CTA) is limited by the diffusion of macro‐radicals within growing grafts. Thus, radical transfer and exchange reactions become inefficient between grafts and free polymer, and convert the surface‐initiated RAFT mechanism to a free radical polymerization. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 1700–1705